Sobre los límites del campo : ensayos de crítica literaria latinoamericanista - Beverley, John, 1943- ([Raleigh] : Editorial A Contracorriente : Department of Foreign Languages and Literatures at North Carolina State University, 2022)
"A collection of selected essays by critic John Beverley in the field of literary Latin Americanism, attentive to the connections between literature, hegemony, and social conflict. It covers the period from the eighties of the last century to today. Topics include the colonial baroque and its hegemonic force in Latin American culture, testimony as an emerging genre, militant literature, postmodernism, the relationship between literary and cultural criticism and the development of the so-called Pink Tide, and in general the impact of postcolonial and subaltern studies. The collection provides a critical vision of the Latin American literate city and a defense of the field of literary criticism as a place to constitute and reconstitute hegemony. In this sense, it stands both against the so-called 'crisis in the humanities' induced by the ideological effects of neoliberalism, but also against critical positions, such as deconstruction, which aspire to a transcendence of literary criticism as such, and of the project of Latin Americanism in general terms"--
La política de la teoría: un itinerario personal (2005) -- La economía política del Locus Amoenus (1983) -- Barroco de estado: Góngora y el gongorismo colonial (1981) -- Anatomía del testimonio (1987) -- El Tungsteno de Vallejo: hacia una reivindicación de la 'novela social' (1989) -- El testimonio en la encrucijada (1993) -- Hay vida más allá de la literatura? (1995) -- Sobre la supuesta modernidad del Apologetico de Juan de Espinosa Medrano (1995) -- Post-literatura: sujeto subalterno e impase de las humanidades (sobre dos textos andinos de la rebelión tupamarista) (1993/1996) -- Algunos apuntes sobre la relación literatura-revolución en el caso nicaragüense (1999) -- Calibán despues del comunismo (2000) -- Algunas observaciones sobre el último ensayo de Antonio Cornejo Polar y el futuro del Hispanoamericanismo (2002) -- El giro neoconservador en la crítica literaria y cultural latinoamericana (2008) -- Sobre el "performance" de Mujeres creando: marginalidad, visibilidad, y Estado (2008) -- El ultraizquierdismo: enfermedad infantil de la academia (2013) -- PD El izquierdismo desde la pandemia (septiembre 2021) -- Despues de lo poscolonial: la igualdad y la crítica literaria en tiempos de globalización (2016) -- Vidas subalternas (2019) -- El fracaso de Latinoamerica (2018) -- Declaración de fundación. Grupo de Estudios Subalternos Latinoamericanos (1982).
Online resource; title from PDF title page (JSTOR, viewed March 20, 2025)
JSTOR
Keywords: Criticism -- Latin America -- History; Latin American literature -- Social aspects -- History and criticism; Latin American literature -- History and criticism; Critique -- Amérique latine -- Histoire; Littérature latino-américaine -- Aspect social -- Histoire et critique; Littérature latino-américaine -- Histoire et critique; Caribbean & Latin American; LITERARY CRITICISM; HISTORY; Criticism; Latin American literature; Latin American literature -- Social aspects; Latin America; Electronic books; Criticism, interpretation, etc; Essays; History; Literary criticism; Essays; Literary criticism; Critiques littéraires.